Application of Sentiment Analysis in Understanding Human Emotions and Behaviour - Saraff, Sweta; Taraban, Roman; Rishipal, Rishipal; Biswal, Ramakrishna; Kedas, Shweta; Gupta, Shakuntala (EAI Endorsed Transactions on Smart Cities, 2020)
INTRODUCTION: Presently, naturalistic observation is considered as critical in understanding, and predicting the complexities of feelings and sentiments. Emerging trends of social media has completely revolutionized the process of communication. Social media, microblogging, and other means of e-communication can be used for extracting the content to decode the quality, valence, and effectiveness of communication. OBJECTIVES: In this paper, we represent the explanatory urge of mental health assessment during a pandemic situation, especially in a smart city scenario. METHODS: We reviewed the role of sentimental analysis, as an emerging application tool for emotional and behavioural analysis for the population affected by a pandemic. This paper examines the prospect of analysing the sentiments through machine learning tools to understand, describe, and predict human behavior. CONCLUSION: Further analysis of this psychological e-content can be used to understand and predict the patterns of human sentiments.
Keywords: Sentiment Analysis; Human Behavior; Emotions; Natural Language Processing